Bood Review: International Case Studies of Terrorist Rehabilitation, : Writer: Rohan Gunaratna, Sabariah M. Hussin (Eds) - Aly Ashghor, Aly Ashghor (Jurnal Keamanan Nasional, 2019)
The post-9/11 rehabilitation programs have become attention in various countries. The projects for terrorism rehabilitation planning programs are systematically and structured carried out in several countries, such as Saudi Arabia, Singapore, Pakistan, Malaysia, Egypt, Iraq, and Uzbekistan. Whilst, this program is conducted through ad hoc institutions in some countries, such as in Nigeria, China, Indonesia, Bangladesh, Denmark, Germany, Britain, and Nepal. The terrorism rehabilitation program of the post-9/11 tragedy tended to be focused on terrorist groups that used Islamic symbols. This book consists of a series of case studies of different terrorist rehabilitation initiatives that have been attempted around the world. Rehabilitation programs in countries are critically analyzed to develop a good understanding of the significance of different approaches and strategies of terrorist rehabilitation in helping potential terrorists to integrate back into society. This book provides vital tools to address the challenges faced by practitioners of terrorist rehabilitation programs.